1987
DOI: 10.1038/bjc.1987.134
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of imaging with antibody to human chorionic gonadotrophin in the detection of residual choriocarcinoma

Abstract: Summary Choriocarcinoma can be imaged by external scintigraphy after intravenous administration of radiolabelled antibody directed against human chorionic gonadotrophin (HCG). The purpose of this study was to investigate whether antibody imaging was sufficiently sensitive and specific to improve the selection of patients for surgical resection of localised deposits of drug resistant or recurrent choriocarcinoma. Eighteen patients with raised serum HCG concentrations in whom the site of tumour was not known wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…A previous report indicated that imaging with antibody directed against hCG can locate deposits of choriocarcinoma and that the method is sensitive and specific enough to be useful clinically (2). We have demonstrated similar clinical value for AI with antibody against aFP in the management of resistant GCT.…”
Section: Case Reportsupporting
confidence: 61%
See 1 more Smart Citation
“…A previous report indicated that imaging with antibody directed against hCG can locate deposits of choriocarcinoma and that the method is sensitive and specific enough to be useful clinically (2). We have demonstrated similar clinical value for AI with antibody against aFP in the management of resistant GCT.…”
Section: Case Reportsupporting
confidence: 61%
“…Recently, we published our experience with AI using antibody against hCG in resistant or recurrent choriocarcinoma (2). In this paper, we report our experience with imaging using antibody directed against aFP in patients with GCT and attempts to define its clinical usefulness.…”
Section: Tumourmentioning
confidence: 99%
“…In contrast, 43% of those patients having a thoracotomy and 71% of those patients having a craniotomy clearly benefited from these surgical procedures. In a number of these patients there are multiple radiological abnormalities still present at the end of chemotherapy and the selection of the anatomical site for surgery can be helped by radioimmunolocalization with anti‐hCG scanning (Begent et al 1987). Even on relapse, the salvage rate with further therapy is still reasonable and 6 (75%) of 8 patients relapsing after EMA/CO therapy have achieved a further sustained remission.…”
Section: Discussionmentioning
confidence: 99%
“…At one point during her disease, hCG was undetectable for 4 months but, when chemotherapy again became necessary, the disease proved to be resistant. Finally, she was transferred to the trophoblastic center at the Charing Cross Hospital in London for radioactive anti-hCG detection (18). This investigation showed multiple minimal metastases in the lungs and the bladder.…”
Section: Metastatic High-riskmentioning
confidence: 99%